New records and extension of the known distribution of some freshwater shrimps in Brazil - Leonardo G Pileggi; Célio Magalhães; Georgina Bond-Buckup; Fernando Mantelatto (Revista Mexicana de Biodiversidad)
Freshwater prawns are distributed in rivers and streams of inland and brackish waters throughout America. In Brazilian waters are registered 35 species into 4 families (Atyidae, Euryrhynchidae, Palaemonidae, and Sergestidae). Information about the geographic distribution of this fauna is scattered in the literature and frequently not founded on documented data in scientific collections. Here we examined a series of specimens and detected several new records and extension of the known distribution of some freshwater shrimps in Brazil.